Moc dowodowa danych udostępnianych na odległość przez centralną informację Krajowego Rejestru Sądowego - Kotecka, Sylwia (Kwartalnik Prawa Publicznego, 2012)
Polish law on the National Court Register has been amended from 1.1.2012 in scope of legal force of data sharing in electronic form by the Central Information of the Register. An electronic copy, extract or certificate issued by the Central Information at the distance have legal force of official document (as well as a paper copy, paper extract or paper certificate) within a court proceedings. The Central Information of the National Court Register gives access by the Internet to the data collected in the Register. They don’t have legal force of document (official or private) but other evidential mean within a court proceedings. If a print of such information fulfills requirements settled by the law, it will be accepted by the court as an official document. Author detailed presents new regulations and submit legal stipulations for the future.